Exploring How Dopants Strengthen Metal-Ni/Ceramic-Al2O3 Interface Structures at the Atomic and Electronic Levels - Fengqiao Sun; Xiaofeng Zhang; Long Li; Qicheng Chen; Dehao Kong; Haifeng Yang; Renwei Li (Molecules)
The metal-based/ceramic interface structure is a key research focus in science, and addressing the stability of the interface has significant scientific importance as well as economic value. In this project, the work of adhesion, heat of segregation, electronic structure, charge density, and density of states for doped-M (M = Ti, Mg, Cu, Zn, Si, Mn, or Al) Ni (111)/Al2O3 (0001) interface structures are studied using first-principle calculation methods. The calculation results demonstrate that doping Ti and Mg can increase the bonding strength of the Ni–Al2O3 interface by factors of 3.4 and 1.5, respectively. However, other dopants, such as Si, Mn, and Al, have a negative effect on the bonding of the Ni–Al2O3 interface. As a result, the alloying elements may be beneficial to the bonding of the Ni–Al2O3 interface, but they may also play an opposite role. Moreover, the Ti and Mg dopants segregate from the matrix and move to the middle position of the Ni–Al2O3 interface during relaxation, while other dopants exhibit a slight segregation and solid solution in the matrix. Most remarkably, the segregation behavior of Ti and Mg induced electron transfer to the middle of the interface, thereby increasing the charge density of the Ni–Al2O3 interface. For the optimal doped-Ti Ni–Al2O3 interface, bonds of Ti–O and Ti–Ni are found, which indicates that the dopant Ti generates stable compounds in the interface region, acting as a stabilizer for the interface. Consequently, selecting Ti as an additive in the fabrication of metal-based ceramic Ni–Al2O3 composites will contribute to prolonging the service lifetime of the composite.